2011
DOI: 10.1121/1.3593366
|View full text |Cite
|
Sign up to set email alerts
|

Learning a novel phonological contrast depends on interactions between individual differences and training paradigm design

Abstract: Studies evaluating phonological contrast learning typically investigate either the predictiveness of specific pretraining aptitude measures or the efficacy of different instructional paradigms. However, little research considers how these factors interact-whether different students learn better from different types of instruction-and what the psychological basis for any interaction might be. The present study demonstrates that successfully learning a foreign-language phonological contrast for pitch depends on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
355
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(399 citation statements)
references
References 62 publications
37
355
7
Order By: Relevance
“…While some of these characteristics may be controlled in the experimental paradigm, they all likely influence the individual's ability to take advantage of any given training paradigm. Perrachione et al (2011) examined the benefit of including high variability training stimuli in a training paradigm designed to teach a novel phonological contrast. They found that listeners who had a high aptitude for learning phonological contrasts (assessed prior to training) benefitted from training stimuli with high variability, whereas low aptitude listeners were negatively impacted by high stimulus variability, and benefitted more from training paradigms where stimuli were blocked by talker.…”
Section: E Benefits Of High Variability Training Stimulimentioning
confidence: 99%
“…While some of these characteristics may be controlled in the experimental paradigm, they all likely influence the individual's ability to take advantage of any given training paradigm. Perrachione et al (2011) examined the benefit of including high variability training stimuli in a training paradigm designed to teach a novel phonological contrast. They found that listeners who had a high aptitude for learning phonological contrasts (assessed prior to training) benefitted from training stimuli with high variability, whereas low aptitude listeners were negatively impacted by high stimulus variability, and benefitted more from training paradigms where stimuli were blocked by talker.…”
Section: E Benefits Of High Variability Training Stimulimentioning
confidence: 99%
“…L2 perception training studies usually aim to improve the perception of "difficult" L2 contrasts, i.e., ones that assimilate to one L1 category (SC or CG, according to Best's PAM, 1995) (e.g., for consonants: Bradlow et al, 1997;Lively et al, 1993;Lopez-Soto and Kewley-Port, 2009;for vowels: Wong, 2013; for tone contrasts: Perrachione et al, 2011). The training procedures have typically involved one or more perception tasks (for example, discrimination and/or identification) where, for example, minimal pairs of words, pseudo words or segments are trained and tested (Bradlow et al, 1997;Lopez-Soto and Kewley-Port, 2009).…”
Section: Perceptionmentioning
confidence: 99%
“…Similarly to Ranta (2008) and Gregersen and MacIntyre (2014), Li suggests that explicit instruction coupled with metalinguistic explanation is more appropriate for beginners, especially those with poor analytic ability, whereas more advanced learners, who are likely to depend more on WM capacity, may benefit from memory strategies which can aid them in processing and retrieving new information as well as reconceptualizing old information. Some work on ATI has been done as well in the case of pronunciation, a good example being the research project by Perrachione, Lee, Ha, and Wong (2011), who explored the interaction between learners' perceptual ability and training of non-native phonological contrasts in an input-variation study. The general conclusion was that different kinds of input, that is such characterized by high as opposed to low variability, can have a differential effect on learners manifesting different levels of phonological aptitude.…”
Section: Foreign Language Aptitudementioning
confidence: 99%